Right to Education: Accessing Education to the Doors of Disadvantaged and Weaker Sections - Rahman, Ashiqur (Journal of Advanced Research in English & Education, 2020)
Education is the single most important instrument for social and economic transformation. Since its independence the Government of India is continuously doing efforts in the direction to attain the goal of Education for all. This act was an appreciable step in which the Government of India has taken the responsibility to provide 6 to 14 years children free and compulsory education in their neighborhood school. This act will certainly a revolution to access education to all children to all section of India, particularly the disadvantaged and weaker section of the highly plural and socially stratified society. The Act has open up the whole sphere of circumstances which come in the way of a child’s enrolment in school and his/ her completion of the elementary stage. This necessilitates an attempt at listing of categories of children who might be covered under section 2(d) and (e) and spelling out of possible strategies to prevent explicit and implicit discrimination in pursuing and completing elementary education. But it will be significant more if the policies and act implemented with full and force in its practical form. How to cite this article: Rahman A. Right to Education: Accessing Education to the Doors of Disadvantaged and Weaker Sections. J Adv Res Eng & Edu 2020; 5(4): 8-11